The interplanetary Internet [networked space communications]. - Jackson, J.
This paper discusses the current debate among NASA engineers on how to best achieve a networked model of interplanetary communications. While there are those who believe that existing Internet protocols can be extended deep into space, others believe that these Internet protocols need to be supplemented with new ones to network remote space.
Keywords: Internet protocols; NASA; TCP/IP.; Antenna; Interplanetary communications; Radio signals; Solar system; Space communications; Telecommunications software